Ultra-processed food consumption among infants in primary health care in a city of the metropolitan region of São Paulo, Brazil - Gláubia Rocha Barbosa Relvas; Gabriela dos Santos Buccini; Sonia Isoyama Venancio (Elsevier, 2019)
Objective: To analyze the prevalence of ultra-processed food intake among children under one year of age and to identify associated factors. Methods: A cross-sectional design was employed. We interviewed 198 mothers of children aged between 6 and 12 months in primary healthcare units located in a city of the metropolitan region of São Paulo, Brazil. Specific foods consumed in the previous 24 h of the interview were considered to evaluate the consumption of ultra-processed foods. Variables related to mothers' and children's characteristics as well as primary healthcare units were grouped into three blocks of increasingly proximal influence on the outcome. A Poisson regression analysis was performed following a statistical hierarchical modeling to determine factors associated with ultra-processed food intake. Results: The prevalence of ultra-processed food intake was 43.1%. Infants that were not being breastfed had a higher prevalence of ultra-processed food intake but no statistical significance was found. Lower maternal education (prevalence ratio 1.55 [1.08-2.24]) and the child's first appointment at the primary healthcare unit having happened after the first week of life (prevalence ratio 1.51 [1.01-2.27]) were factors associated with the consumption of ultra-processed foods. Conclusions: High consumption of ultra-processed foods among children under 1 year of age was found. Both maternal socioeconomic status and time until the child's first appointment at the primary healthcare unit were associated with the prevalence of ultra-processed food intake. Resumo: Objetivo: Analisar a prevalência do consumo de alimentos ultraprocessados entre crianças com menos de um ano e identificar os fatores associados. Métodos: Foi realizado um estudo transversal. Entrevistamos 198 mães de crianças com idades entre 6 e 12 meses em unidades de atenção primária à saúde localizadas em Embu das Artes, uma cidade da região metropolitana de São Paulo, Brasil. Alimentos específicos consumidos nas 24 horas anteriores à entrevista foram considerados para avaliar o consumo de alimentos ultraprocessados. As variáveis relacionadas às características das mães e crianças e as unidades de atenção primária à saúde foram agrupadas em três blocos de influência cada vez mais proximal com o resultado. Foi realizada uma análise de regressão de Poisson de acordo com um modelo estatístico hierárquico para determinar os fatores associados ao consumo de alimentos ultraprocessados. Resultados: A prevalência de consumo de alimentos ultraprocessados foi 43,1%. As crianças que não eram amamentadas apresentaram maior prevalência de consumo de alimentos ultraprocessados, porém não foi encontrada diferença estatística. Menor nível de escolaridade materna (RP 1,55 [1,08-2,24]) e o fato de a primeira consulta da criança na unidade de atenção primária à saúde acontecer na primeira semana de vida (RP 1,51 [1,01-2,27]) foram fatores associados ao consumo de alimentos ultraprocessados. Conclusões: Foi encontrado consumo elevado de alimentos ultraprocessados entre crianças com menos de um ano. A situação socioeconômica materna e o tempo da primeira consulta da criança na unidade de atenção primária à saúde foram associados à prevalência de consumo de alimentos ultraprocessados. Keywords: Complementary feeding, Infant feeding practices, Primary health care, Ultra-processed food, Palavras-chave: Alimentação complementar, Práticas de alimentação infantil, Atenção primária à saúde, Alimento ultraprocessado